Industry of employment and occupational class in relation to cardiovascular health by race/ethnicity, sex/gender, age and income among adults in the USA: a cross-sectional study - Symielle A Gaston; Chandra L Jackson; Jamie A Murkey; Dana M Alhasan; W Braxton Jackson (BMJ Public Health)
Background Racially minoritised groups tend to have poorer cardiovascular health (CVH) than non-Hispanic (NH)-White adults and are generally more likely to work in labourer or support service positions where job strain—associated with cardiovascular disease—is often high. Yet, few studies have included racially/ethnically diverse samples.Methods Using 2004–2018 National Health Interview Survey cross-sectional data, we investigated standardised occupational classifications in relation to ‘ideal’ CVH using a modified ‘ideal’ CVH (mICVH) metric among US adults (n=230 196) by race/ethnicity, sex/gender, age, and income. mICVH was defined as a report of ‘yes’ to the following: never smoked/former smoker; body mass index (≥18.5–25 kg/m2); physical activity (≥150–300 min/week moderate or ≥75–150 min/week vigorous); sleep duration (7–9 hours/night); and no prior diagnosis of dyslipidaemia, hypertension, or diabetes/pre-diabetes. Adjusting for sociodemographic, clinical factors, and health behaviour confounders, we used Poisson regression with robust variance to estimate prevalence ratios (PRs) and 95% CIs of mICVH overall and by race/ethnicity and performed Wald tests for interaction.Results Latinx (53%) and NH-Black (37%) adults were more likely than NH-White adults (29%) to report labourer positions and had the lowest prevalence of mICVH (5.2% (Latinx) and 3.9% (NH-Black)). Labourer versus professional/management occupational class positions were associated with a lower mICVH prevalence among NH-Asian (PR=0.60 (0.46–0.79)), NH-White (PR=0.80 (0.74–0.87)) and NH-Black (PR=0.77 (0.58–1.01)), but with no evidence of an association among Latinx (PR=0.94 (0.78–1.14) adults; p interaction <0.001).Conclusions In conclusion, working in labourer versus professional/management positions was associated with lower mICVH, except among Latinx adults. Given the higher likelihood of labourer occupations and lower prevalence of mICVH among minoritised racial/ethnic groups, social determinants related to occupational class should be considered in future studies of racial and ethnic disparities in CVH.